2017
DOI: 10.1002/aqc.2770
|View full text |Cite
|
Sign up to set email alerts
|

Archipelago Los Roques: A potential baseline for reef fish assemblages in the southern Caribbean

Abstract: 1. Despite increasing policies of protection, few localities in the Caribbean remain spared from human impacts. These lightly affected areas can better reflect the past composition of reef fish assemblages and provide baseline information about the natural factors driving fish distributions in the region. 2. Reef fish assemblage structures were analysed in 21 Caribbean fished areas and marine protected areas (MPAs) along a gradient of distance to the nearest major market place. Assemblage structures by size an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 94 publications
(188 reference statements)
0
3
0
Order By: Relevance
“…We found that sites such as DMS and FAR supported 4-6 times more fish biomass and 1.5-fold higher species richness compared to CAY, where the habitat was flatter and less structurally complex and the fish assemblage comprised mostly small demersal species like Stegastes partitus and Thallassoma bifasciatum. These species are considered omnivorous and generalist, often associated with degraded sites with low complexity and where competition with other species of damselfish is limited (Dominici-Arosemena and Wolff, 2006;Elise et al, 2017). Our results also indicated that only a few massive coral species (e.g., Orbicella faveolata, O. annularis, and Colpophyllia natans) contributed to live coral cover while increasing habitat structural complexity.…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…We found that sites such as DMS and FAR supported 4-6 times more fish biomass and 1.5-fold higher species richness compared to CAY, where the habitat was flatter and less structurally complex and the fish assemblage comprised mostly small demersal species like Stegastes partitus and Thallassoma bifasciatum. These species are considered omnivorous and generalist, often associated with degraded sites with low complexity and where competition with other species of damselfish is limited (Dominici-Arosemena and Wolff, 2006;Elise et al, 2017). Our results also indicated that only a few massive coral species (e.g., Orbicella faveolata, O. annularis, and Colpophyllia natans) contributed to live coral cover while increasing habitat structural complexity.…”
Section: Discussionmentioning
confidence: 50%
“…Severe bleaching events leading to rapid loss of coral cover have impacted several coral populations in Los Roques (Villamizar et al, 2008;Bastidas et al, 2012), and Los Roques also suffered the loss of most of the reef building Acropora palmata populations in past years (Croquer et al, 2016). Nevertheless, coral reefs in this MPA still support fish abundance that is above the Caribbean average (Elise et al, 2017). This finding highlights the ecological importance of this MPA at the regional scale for there is increasing evidence indicating that Caribbean reefs are losing most of their structural complexity (Alvarez-Filip et al, 2009) and concomitantly fish communities have changed rapidly (Alvarez-Filip et al, 2009, 2015.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation